ANALISIS PENYEBAB KECELAKAAN KERJA STUDI KASUS: KAPAL TONGKANG MENABRAK KAFE DI PINGGIR SUNGAI - Safira Aulia; Ahmad Mustofa (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
The purpose of this study is to analyze the causes of a work accident involving a coal barge that hit a cafe on the banks of the Mahakam River, Samarinda, and to provide recommendations to prevent similar incidents. In this study, the data used is secondary data using literature and reports related to the incident. The research method applied is a qualitative approach with a literature study, which allows for in-depth analysis of the phenomenon without direct field data collection. The main factors of this accident are: (1) human negligence (2) equipment damage and (3) extreme weather conditions. The impact of this accident includes severe damage to the cafe building, financial losses for the business owner, disruption of business operations, and psychological trauma for visitors and employees. As a preventive measure, this study recommends the installation of barriers on the riverbank, routine inspection and replacement of ship connecting ropes, installation of rope tension sensors for early detection of damage, and training of ship crews in dealing with bad weather conditions. This study highlights the importance of implementing occupational safety standards to reduce the risk of accidents in the water transportation sector